Improved biochemical properties of roots of selected economic crops after simulated microgravity impact - Oluwafemi, Funmilola A.; Ibraheem, Omodele; Olubiyi, Afolabi R. (Frontiers in Space Technologies, 2025)
Introduction: Microgravity science involves studies of physical phenomena in which the Earth’s-gravity is significantly decreased, and these have given uniquely-new advancements towards understanding cellular metabolic processes. Under this status, plants have developed cellular readjustment mechanisms that allows adaptation to these external physical factors. Peanut (Arachis hypogaea L.), corn (Zea mays) and tomato (Solanum lycopersicum) are essential economic crops; with nutritional, medicinal and economic-values of the seeds, germinated roots and seedlings.Methods: In this study, the effects of simulated microgravity (using Clinostat) on peanut, corn and tomato germinated roots were investigated on the resistance of abiotic salinity [NaCl; 30 mM–100 mM] and heavy metal [Pb(NO3)2; 30 mM–100 mM] through antioxidants assay, and activities of root germination and elongation enzymes. The simulated microgravity equipment used in this project is a two-dimensional (2D) Clinostat. The antioxidant-potentials were done using DPPH (2,2-diphenylpicrylhydrazyl), FRAP (Fluorescence Recovery After Photobleaching) and ABTS (2,2-azinobis-(3-ethylbenzothiazoline-6- sulfonic acid) assays. The root germination enzymes (alpha-amylase and lipase) and root elongation enzyme (beta-glucanase) activities were determined and read with ELISA (Enzyme-Linked-Immunosorbent Serologic Assay) spectrophotometer.Results: Results revealed that simulated-microgravity root samples had significantly better antioxidant-potentials than control for all the selected crops. Also, all the unstressed and stressed simulated microgravity samples had significant higher enzyme activities than the gravity (unstressed and stressed) samples.Discussion: The collection and analysis of these root samples provided a valuable resource of improved biochemical properties of the simulated microgravity samples.